Methods of macrophages activation and their modulation for the prospection of new antileishmania drugs: a review (Bioscience Journal, 2021)
Leishmaniasis are a group of parasitic zoonoses provoked by protozoa from Leishmania genus and belonging to the group of neglected tropical diseases. The search and development for new drugs is necessary not only to investigate the activity against only the parasite, but also to investigate the possible synergistic effect of new drugs with the immune response of the host. In the present review, macrophages are pointed out as potential targets of the investigation of new antileishmanial drugs, and some methodologies in order to assess their activation as response to Leishmania-infected cells are presented. Macrophages are an important role in the cellular immune response, since they are cells from mononuclear phagocytic system, the first line of defense of the host, against parasites from Leishmania genus. Phagocytic capacity, lysosomal activity, increase of nitric oxide and intracellular calcium levels are parameters regarding assessment of macrophages activation which allow them to be more hostile in order to solve the infection and lead the patient to cure. In this context, we bring 19 substances already investigated and that activate macrophages, what makes them promising in the antileishmanial treatment. Therefore, assessment of macrophages activation, are important tools for discovery of immunomodulatory compounds which have potential to act in synergism with host immune response. Such compounds might be promising as monotherapy in the treatment of leishmaniasis, as well as being used as adjuvants in vaccines and/or in combination with conventional drugs.